Influence of drying methods to quality of meniran herb (Phyllanthus niruri LINN.) - Rivai, Harrizul; Nurdin, Hazli; Suyani, Hamzar; Bakhtiar, Amri (Indonesian Journal of Pharmacy, 2011)
Effects of drying methods in obtaining the extractive, phenolic content and antioxidant activity in Phyllanthus niruri Linn. herbs have been investigated. The drying  methods  tested  were  air-drying  at  ambient  temperature,  oven-drying  at 40  °C,   oven-drying  at  60  °C,  and  fresh  samples  as  control.  Results  revealed that  drying  of  the  fresh  plant  caused  the  decrease  of  extractive  obtainability, phenolic  content  and  antioxidant  activity.  There  were  significant  differences among drying  methods (p < 0.05). Among the drying methods tested, the best result was by oven-drying at 40 °CKey words: Antioxidant, Phyllanthus niruri Linn., drying methods, phenolic compounds